Culture conditions effect properties of the Na+/K+-ATPase pump current in hiPSC cardiomyocytes. (24th May 2021) - Ismaili, D; Gurr, K; Horvath, A; Hansen, A; Eschenhagen, T; Christ, T
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): BMBF Background: Cardiomyocytes derived from human induced pluripotent stem cells (hiPSC) provide an opportunity to study human cardiac physiology and pathophysiology or to use for cardiac repair as well as for cardiovascular drug testing. Suitability for these purposes requires generating hiPSC cardiomyocytes that share typical electrophysiological properties of adult human cardiomyocytes. In the human heart the Na+/K+-ATPase pump current plays a major role in the regulation of contractile force and electrical stability. So far there are no data about Na+/K+-ATPase pump current function in hiPSC cardiomyocytes available. Purpose: We compared the properties of Na+/K+-ATPase pump current in hiPSC cardiomyocytes from conventional monolayers (ML) culture to three-dimensional engineered heart tissue (EHT). Methods: HiPSC cardiomyocytes differentiated from in-house control hiPSC cell line C25 were dissociated from ML and EHT culture. Na+/K+-ATPase pump current was recorded by whole-cell patch clamp technique at 37°C. The holding potential was -40 mV to inactivate sodium current. Current was measured in the absence of K+ and after adding 5.4 mM potassium chloride (KCL). Na+/K+-ATPase pump current was defined as the ouabain (10 µM) sensitive current. Voltage-dependency of Na+/K+-ATPase pump was determined using rectangular voltage pulses (increasing from -120 mV to +60 mV). Results: Outwardly directed Na+/K+-ATPase pump could be recorded at -40 mV when KCL was added to the bath solution (5.4 mM). Currents were larger in EHT than in ML (0.8 ± 0.08 pA/pF n = 16 ML vs. 1.29 ± 0.13 pA/pF n = 28 EHT; p < 0.05). The K+-induced outward current was abolished by ouabain. The K+- and ouabain-sensitive current densities were similar in size (0.84 ± 0.11 pA/pF n = 16 ML vs. 1.12 ± 0.11 pA/pF n = 28 EHT for ouabain), indicating the measured K+-induced current was Na+/K+-ATPase pump current. Increasing extracellular K+-concentration in a stepwise manner (0, 25 mM, 0, 5 mM, 1 mM, 2 mM, 5, 4 mM and 10 mM) showed a concentration-dependent relationship to Na+/K+-ATPase pump current with throughout higher current densities in EHT compared to ML (sensitivity to K+ not different). Na+/K+-ATPase pump current showed expected voltage-dependency with +0.23 ± 0.13 pA/pF at -120 mV and +0.89 ± 0.16 pA/pF at +60 mV (n= 18) in ML and with +0.71 ± 0.17 pA/pF at -120 mV and +1.2 ± 0.2 pA/pF at +60 mV (n= 24) in EHT. Conclusion: HiPSC cardiomyocytes possess Na+/K+-ATPase pump current. Current density is in the range of human cardiomyocytes in EHT but substantially smaller in ML. 3D culturing may be needed to develop the physiological properties of Na+/K+-ATPase pump current.